Repetitive Transcranial Magnetic Stimulation Coupled With Visual-Feedback Cycling Exercise Improves Walking Ability and Walking Stability After Stroke: A Randomized Pilot Study - Yixiu Wang; Xiaoming Chen; Menghuan Wang; Yingying Pan; Shiyi Li; Mengfei He; Feng Lin; Zhongli Jiang (Neural Plasticity)
Conclusion: The combination of rTMS and cycling exercise effectively improves walking ability and walking stability in patients with stroke, which may be related to the excitability modulation of the motor cortex induced by rTMS.